Building resilience in practice to support coral communities in the Western Indian Ocean. Issue 106 (April 2020) - Hattam, Caroline; Evans, Louisa; Morrissey, Karyn; Hooper, Tara; Young, Kathy; Khalid, Fazlun; Bryant, Mark; Thani, Ali; Slade, Lorna; Perry, Chris; Turrall, Susanne; Williamson, Dominica; et al.
Highlights: Multiple strategies used to build resilience of coral reefs and reef dependent communities. Intended and realised social and ecological implications of strategies explored. Disaggregated understanding of ecological and social resilience is needed. Policy must encourage strategies contributing across the social-ecological spectrum. Clear opportunity to strengthen knowledge networks and sharing. Abstract: Global environmental change and other site specific pressures (e.g. over fishing and pollution) are threating coral reefs and the livelihoods of dependent coastal communities. Multiple strategies are used to build the resilience of both coral reefs and reef dependent communities but the effectiveness of these strategies is largely unknown. Using the Western Indian Ocean (WIO) as a case study, this paper combines published literature and expert opinion elicited through a multi-stakeholder workshop to assess the intended and realised social and ecological implications of strategies commonly applied in the region. Findings suggest that all strategies can contribute to building social and ecological resilience, but this varies with context and the overall strategy objectives. The ability of strategies to be successful in the future is questioned. To support effective resilience policy development more nuanced lesson learning requires effective monitoring and evaluation as well as a disaggregated understanding of resilience in terms of gender, agency and the interaction between ecological and social resilience. Opportunities for further lesson sharing between experts in the region are needed.